Efeito in vitro do extrato de Solanum sessiliflorum: atividade antioxidante e antitumoral (MCF-7 e HT29) - Montagner, Greice Franciele Feyh dos Santos (2015)
Epidemiological studies have suggested that intake of fruits and vegetables act in the prevention of several diseases such as cancer and cardiovascular diseases. This can be explained by these bioactive compounds are present in their food nutritional matrix that may have different biological activities, including antioxidant, antitumor, genoprotective and in preventing the oxidation of LDL. However, much of the fruit remains to be studied. This is the case of Solanum sessiliflorum popularly known as mana-cubiu or cubíu fruit coming from the Amazon region of Brazil, considered the "Amazonian apple". This fruit is popularly used as a medicine to control the itching of the skin and reducing cholesterol levels, glucose and uric acid in the blood. Once S. sessiliflorum studies are still incomplete, the aim of this study was to chemically characterize the extract and perform tests to determine their prospecting potential antioxidant, antitumoral and effect in vitro on preventing the oxidation of LDL. For this, the study was conducted in two stages, the first stage was prepared hydroalcoholic extract of the peel and seed and pulp. After preparation of the extract, the chemical characterization was conducted by the same determination of total bioactive compounds (flavonoids, tannins and polyphenols), then the extract was chemically characterized by high performance liquid chromatography (HPLC). In the second step, we evaluated the antioxidant potential and in citoprotetor in and in PBMC (Peripheral Blood Mononuclear Cells) and human plasma exposed to hydrogen peroxide (H2O2). We also evaluated the antitumor activity in lines of breast (MCF7) and colorectal (HT29) cancer cell cancer, assessing cell proliferation and viability. After this, the effect has been evalueted on the oxidation of LDL (isolated from healthy individuals). The results obtained indicate that the extract of Solanum sessiliflorum presents in its composition total bioactive compounds such as flavonoids, tannins and polyphenols. These results corroborate the analysis performed by HPLC which indicated that the extracts present in its composition gallic acid, caffeic acid, quercetin, rutin, β carotene and catechin (the latter except in the pulp and seed extract). When examined the in vitro antioxidant effect was observed that extracts at different concentrations did not show any pro-oxidant potential. However extract the pulp and the seeds had antioxidant and cytoprotective activity. It was also observed that the extract of the pulp and the seeds had antigenotoxic and specific antitumor activity for colorectal cancer cells (in vitro tests performed with strain HT29 cells), and no antitumor activity was observed for breast cancer cells (MCF7), instead of the expected high concentrations in the extract increased the viability and proliferation. Another important finding was that both extracts, seeds and pulp and peel showed potential for inhibiting oxidation of LDL. In synthesis, the in vitro results obtained data indicate that S. sessiliflorum has antioxidant, antitumor and citoprotetor activity and present potential to inhibit the oxidation of LDL. These results should be proof of the presence of bioactive compounds in its composition as flavonoids, polyphenols and catechins. In literature there are several studies that report that eating foods rich in these types of compounds are related to the prevention of several chronic diseases, such as cancer and cardiovascular diseases.